2021
DOI: 10.11591/ijphs.v10i4.20924
|View full text |Cite
|
Sign up to set email alerts
|

Vector control Aedes sp. during pandemic COVID-19

Abstract: During the coronavirus disease 2019 (COVID-19) outbreak in Indonesia, the government also faces another health problem, namely dengue hemorrhagic fever (DHF). The routine activities of the dengue management system have been significantly curtailed as government authorities concentrate more on containing the transmission of the COVID-19. This study aimed to describe vector control <em>Aedes sp.</em> during pandemic COVID-19, such as community activities in controlling breeding places, area risk, vec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…Cabe resaltar que nuestra experiencia operativa de adaptación en las acciones de control y reajuste del manejo integrado de vectores, se suma a los trabajos realizados en otras ciudades, como Yogyakarta en Indonesia, y en Malasia, los cuales modificaron y ajustaron las medidas de control y prevención de vectores durante la pandemia, asumiendo retos similares en cuanto a la planeación, modificación y reajuste de actividades de fumigación, distribución de ovitrampas y acoplamiento de actividades comunitarias 26 , 27 .…”
Section: Discussionunclassified
“…Cabe resaltar que nuestra experiencia operativa de adaptación en las acciones de control y reajuste del manejo integrado de vectores, se suma a los trabajos realizados en otras ciudades, como Yogyakarta en Indonesia, y en Malasia, los cuales modificaron y ajustaron las medidas de control y prevención de vectores durante la pandemia, asumiendo retos similares en cuanto a la planeación, modificación y reajuste de actividades de fumigación, distribución de ovitrampas y acoplamiento de actividades comunitarias 26 , 27 .…”
Section: Discussionunclassified
“…Research in Semarang shows a relationship between container colour and the presence of Aedes aegypti larvae used by people in endemic and non-endemic areas of DHF. However, other studies have also shown that brightly coloured containers can potentially become breeding grounds for Aedes Sp larvae if they are never cleaned or tightly closed (Pascawati et al, 2021;Pascawati, 2015;Nur et al, 2018).…”
Section: Field Testmentioning
confidence: 99%
“…Even so, this tool can facilitate survey activities with a faster time of 112.14 seconds -208.67 seconds compared to visual observations. The results of the evaluation of the work of the tool in reducing the level of larval density (HI, CI, and BI) in the environment based on the size of the density figure gave significant results, namely the HI high category (scale 8) fell to the moderate category (scale 2), the CI value from the high category (scale 8) is in the moderate category (scale 3), the BI value is in the high category (scale 6) is in a low category (scale 1) (Pascawati et al, 2021;Miller et al, 1992).…”
Section: Field Testmentioning
confidence: 99%